A multi-robot coordination approach for autonomous runway Foreign Object Debris (FOD) clearance - KUZUCUOĞLU, AHMET EMİN (ELSEVIER SCIENCE BV, 2016)
This paper introduces an effective Foreign Object Debris (FOD) clearance system based on multi-robot coordination. The main objective of this study is to minimize the amount of time airports need to close for the execution of the FOD collection process. At the present time, FOD collection is done by human-operated follow-me vehicles, which is time consuming, expensive and error-prone. Time is a very critical parameter for the aviation domain and a delay of even one minute may cause the failure of a critical military mission or the loss of thousands of dollars at civil aviation. To this end, a multi-robot coordination approach based on auction-based task allocation is proposed in order to handle dynamic task occurrences on the runways of an airport. Robots that are located at stations are coordinated to collect active FOD in the shortest time. An agent-based experimental simulation framework is developed and several FOD collection scenarios are executed on Istanbul Ataturk Airport. The proposed model, which is based on effective robot locating by using heat maps and optimal task assignments, has provided promising results when compared to existing well-known techniques. Application of this study will enable a fully autonomous, safe and fast system that collects FOD, and human-operated vehicles will no longer be needed. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Foreign Object Debris (FOD); Multi-Robot Task Allocation (MRTA); Runway safety; Autonomous systems; TAXONOMY